Familia de productos de diseño industrial para la estimulación creativa de los niños de 6 a 8 años - Morales Barroso, Evelyn Guadalupe (2024)
This project seeks mainly to design industrial design products oriented to stimulate creativity in children within an academic environment. The educational reality in Ecuador faces difficulties in adapting to changing needs over time. The Ministry of Educa tion has expressed concern and desire for improvement, but this has not been reflected in the growth and performance of students, both academically and individually. On the other hand, the increasing integration of technology in the daily lives of children , which has left aside recreational activities, playful activities, and collective games. In short, it is vital to analyze this situation, which offers a limited selection of industrial design products aimed at promoting imagination and the development of skills. The project aims to benefit children from 6 to 8 years old from the Centro Psicopedagógico "Tiempo de Aprender" located in the Province of Tungurahua, through the design of a family of industrial design products that are oriented to stimulate creativity allowing children to solve problems, develop their full potential and understand the why of things. Throughout the design process, the active participation of the different actors involved in this problem is sought, which will allow a deeper understanding of the needs of children, facilitating a more effective intervention in all aspects with greater relevance.